Dual-source powered nanomotor with integrated functions for cancer photo-theranostics. (September 2022) - Chen, Shuqin; Sun, Xiang; Fu, Mingming; Liu, Xiaoxia; Pang, Shiyao; You, Yongqiang; Liu, Xiaojia; Wang, Yong; Yan, Xiaohui; Ma, Xing
Abstract: While the miniaturization and motility of artificial nanomotors made them popular tools for exploring novel and innovative biomedical cancer treatment strategies, the integration of multiple functions on the small motor bodies is key to achieve further progress but remains unresolved. Here, we propose a dual-source powered Janus nanomotor whose composition integrates multiple photo-theranostic functions such as surface-enhanced Raman scattering (SERS) sensing, fluorescence imaging/photoacoustic imaging (PAI), photodynamic therapy (PDT), and photothermal therapy (PTT). This nanomotor can be fabricated by sputtering a thin gold layer onto one side of mesoporous silica (mSiO2 ) combined with surface modification by photo-sensitizer, Raman reporter, and catalase. Upon illumination with 808 nm near-infrared light, the half-coated gold nanoshell serves as PAI/PTT agent, and by upconverting NIR to visible light, the pre-loaded photosensitizer can be excited by the upconverted light of UCNPs to convert the dissolved oxygen (O2 ) into reactive oxygen species for efficient PDT. Furthermore, ratiometric SERS signal can be captured to quantitatively detect the tumor marker, H2 O2, in cellular microenvironments. The immobilized catalase as a nano-engine can catalyze endogenous H2 O2 to O2 . This function not only improves the hypoxic tumor microenvironment and therefore enhances PDT efficiency, but also provides a thrust force for deep penetration. As a proof of concept for the in vivo trial we performed cancer photo-theranostics where our nanomotors successfully treated a mouse breast tumor in a subcutaneous tumor model. The results are promising and encourage the use of an integrated nanomotor platform that could be further developed into a photo-theranostic agent for superficial cancer treatment.